Impact Of Establishment Of Beheshtabad Tunnel On Shahrekord Aquifer - Alimohammadi, Rahim (The Turkish Online Journal of Design Art and Communication, 2016)
Disturbing balance between supply and demand for water in different societies has raised the issue of inter-basin water transfer that associates one of the primitive, outdated and expensive way. In order to clarify the minimal impact of Beheshtabad tunnel that passes at depth of 300 meters below ground level at the Shahrekord plan, this research project was conducted for two years in the region. To facilitate the issue, software Modfow was used and also water balance equation was used for simulating the behavior and reaction of the Shahrekord plain groundwater. Due to the limited thickness of the aquifer and aquifer negative during water balance during the past 8 years (from 2007) which have received a drop of at least equal to 15.5 m, Beheshtabad tunnel with a length of 65 km, diameter of 4 meters and two access tunnels in Shahrekord plain and existence of many faults in the region that act as a powerful drain, and in less than 300 days, the tunnel can discharge the whole water stored in several centuries across the aquifer, upon evacuation of groundwater and entry of air in the empty space, the earth layers will become dense and ground collapse will occur. The minimum water requirement of the region (without considering the development in the area) is 236 million cubic meters annually.
Keywords: inter-basin water transfer; water balance equation; Beheshtabad tunnel; Jahanbin catchement area; Shahrekord plain